Transition metal salts of quinoline: synthesis, structure and magnetic behavior of (QuinH)2[MX4]·2H2O [Quin = quinoline; M = Mn, Co, Cu, Zn], (QuinH)2[MnBr2(H2O)2](Br)2 and (QuinH)[Cu(Quin)Br3]. Issue 20 (18th October 2018) - Landee, Christopher P.; Monroe, Jeffrey C.; Kotarba, Robert; Polson, Matthew; Wikaira, Jan L.; Turnbull, Mark M.
Abstract: A family of compounds of general formula (QuinH)2 MX4 ·2H2 O has been prepared and characterized [Quin = quinoline; M, X = Co, Cl (1 ); M, X = Co, Br (2 ); M, X = Zn, Br (3 ); M, X = Mn, Cl (4 )]. The complexes crystallize in the monoclinic space group C2/c as well-isolated layers containing the MX4 −2 anions and water molecules, separated by the quinolinium cations. The bromide analogue of4, compound5 (QuinH)2 [MnBr2 (H2 O)2 ](Br)2, also crystallizes in the C2/c space group, but comprises a co-crystal of manganese bromide dihydrate and quinolinium bromide. The temperature dependent magnetic properties of the complexes are described, along with the tetrachlorocuprate analogue (7 ). All compounds show weak antiferromagnetic interactions (J/kB ∼ 0.06–1.4 K) and good one- or two-dimensional isolation. In addition, the crystal structure of the mixed quinoline/quinolinium complex (QuinH)[Cu(Quin)Br3 ] (triclinic, P-1) is reported. Graphical Abstract: